Turkey as an intermediary in ensuring stable peace in the world - Yarmukhamedova Irodakhon Nosir kizi (Genius Journals, 2023)
Peacebuilding is a process that deals with physical and institutional instability, responds to people's insecurity, poverty and social justice, combats nationalism or sectarianism, solves economic stagnation and environmental problems, and strengthens infrastructures and communities. This can include hard (military) power and soft power (through persuasion and communication). Due to the changes in the international system, the field for new powers has emerged, which in turn has created a fertile ground for instability, regional conflicts and competition. In this context, emerging powers such as Russia, China, Turkey or the rich Gulf states have become active in increasing instability in the region. They have also become more active as peacebuilders, testing and advocating visions of peacebuilding based on principles, methodologies, and outcomes that differ markedly from those associated with liberal peace.
Keywords: Turkey; NATO; UN; Security Council